Influence of Light Source and Photopolymerization Distance on Composite Resin Microhardness - Furtado Piras, Fernanda; Jendiroba Faraoni, Juliana; Guenka Palma-Dibb, Regina (Journal of Dentistry And Oral Implants, 2016)
The present study evaluated in vitro the influence of two light sources in composite resin microhardness in different distances of photopolymerization. Two light sources were used (halogen, LED) to photopolymerize the composite resin (Filtek Z250; Esthet-X) in different distances surface (1,2,3 and 4 mm), totalizing 96 specimens. Microhardness Knoop test’ were made on the specimens top and bottom faces. The data were submitted to ANOVA and Fisher tests (α=5%). It was observed a significant difference (p<0.05) between the resins, in which Z250 presented higher values than Esthet-X (p<0.05). There was difference also between the halogen and LED, where the halogen showed better results with Z250 and the LED with Esthet-X. The top surface presented better value (p<0.05) compared to the bottom surface. It can be concluded that the light source and the photopolymerization distance influenced the composite resin microhardness, which it had lower proprieties with increase of the photopolymerization distance.
Keywords: Composite resins; polymerization; hardness tests.